Perencanaan Campuran Lapis Aspal Beton Permukaan Dengan Asbuton Butir Sebagai Filler - Surat Surat; Rifanie Gazalie; Pazilatul Mumamiroh (Jurnal Teknik Sipil, 2018)
The objective of this research was to use mineral in asbuton as filler and asphalt will be taken into account to reduce the use of oil asphalt in Asphalt Concrete Wearing Course. The material used in this research was aggregate crushed stone from Katunun Mountain, Tanah Laut Regency, South Kalimantan, asphalt Pen 60/70 production of Pertamina and Asbuton grade 15/20. Use of Asbuton 7% in Asphalt Concrete Wearing Course mixture with optimum asphalt content of 5.25% mixed properties of VIM 3.5%, VMA 15.7%, VFB 77,9%, Stability 1484 kg, Flow 3.3 mm, VIM PRD 3.0%, Stability remaining 90.8% obtained. At the optimum asphalt content of 5.25%, mixed experiments with Asbuton grains were varied, 5.0%, 9.0%, 11.0% and 13.0%. The Marshall test showed that the greater the addition of Asbuton, the higher the stability value, the sequential stability value of 1058 kg, 1449 kg, 1509 kg and 1600 kg. Flow range from 3.1 mm to 3.5 mm. The VIM 3.5% up to 5.6%, VMA 15.75% up to 16.87%, VFB 68.1% up to 71.9%. The experimental results with Marshall testing of the asphalt mixture qualities meet the Asphalt Concrete Wearing Course criteria.